Policy Strategy and Challenges of BIM Implementation in National-Scale Public Construction Project Procurement and Implementation - Puspita, Nurkhasanah Rina; Sitorus, Henry Baginda Polianus (Riwayat: Educational Journal of History and Humanities, 2025)
The rapid digital transformation of the construction sector has positioned Building Information Modeling (BIM) as a key instrument in improving efficiency, transparency, and collaboration in public construction projects. This study explores the policy strategies and challenges of implementing BIM within national-scale public construction procurement and execution in Indonesia. The main objectives are to analyze existing national policy strategies, identify key challenges hindering implementation, and propose strategic policy recommendations. The research employs a qualitative approach using a literature study method, synthesizing findings from academic journals, government regulations, and institutional reports published between 2019 and 2025. Data were analyzed using content and thematic analysis, categorized into three main themes: policy strategy, implementation challenges, and policy recommendations. The results show that Indonesias government has made significant progress in integrating BIM through regulatory enforcement, standardization initiatives, and capacity-building programs. However, implementation remains inconsistent due to uneven technological infrastructure, insufficient human resources, limited interoperability, and financial barriers among contractors. The study recommends developing a National BIM Roadmap, enhancing data management systems, strengthening BIM education and professional certification, and providing fiscal incentives to promote compliance. These findings highlight that effective BIM implementation requires not only regulatory support but also institutional collaboration and long-term investment in digital infrastructure and human capital.